2009
DOI: 10.1161/circulationaha.108.788653
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Restore Renal Function in Chronic Experimental Renovascular Disease

Abstract: Background-Endothelial progenitor cells (EPCs) promote neovascularization and endothelial repair. Renal artery stenosis (RAS) may impair renal function by inducing intrarenal microvascular injury and remodeling. We investigated whether replenishment with EPCs would protect the renal microcirculation in chronic experimental renovascular disease. Methods and Results-Single-kidney hemodynamics and function were assessed with the use of multidetector computed tomography in vivo in pigs with RAS, pigs with RAS 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
222
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 204 publications
(241 citation statements)
references
References 54 publications
17
222
0
2
Order By: Relevance
“…Their mobilization from bone marrow and recruitment to the injured kidney is regulated by the release of homing factors such as stromal cell-derived factor (SDF)-1 and stem cell factor (SCF). Our group has demonstrated that delivery of EPC in the stenotic ARVD kidney improved renal hemodynamic and function and decreased the release of endogenous injury signals from the stenotic kidney [15,16]. In line with these observations, we have shown in swine ARVD that intra-renal delivery of autologous hematopoietic EPC during PTRA improved renal hemodynamics and function in the post-stenotic kidney [17].…”
supporting
confidence: 72%
“…Their mobilization from bone marrow and recruitment to the injured kidney is regulated by the release of homing factors such as stromal cell-derived factor (SDF)-1 and stem cell factor (SCF). Our group has demonstrated that delivery of EPC in the stenotic ARVD kidney improved renal hemodynamic and function and decreased the release of endogenous injury signals from the stenotic kidney [15,16]. In line with these observations, we have shown in swine ARVD that intra-renal delivery of autologous hematopoietic EPC during PTRA improved renal hemodynamics and function in the post-stenotic kidney [17].…”
supporting
confidence: 72%
“…Such injury may respond to alternative or adjunctive interventions to modify repair pathways independent of large vessel hemodynamics. As an example, recent studies using endothelial progenitor cells in experimental ARAS demonstrate restoration of both microvascular structures and GFR using cell-based therapy (40). Furthermore, delivery of adipose-derived mesenchymal stem cells in conjunction with revascularization of experimental ARAS demonstrate anti-inflammatory potential and improved efficacy of revascularization (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, transplanted EPCs have been shown to induce angiogenesis and restore the function of ischemic tissue. 21,22 Importantly, like other ECs, EPCs can form robust vessel networks in engineered tissue constructs in the presence of stromal cells, and can be functional in vivo for up to 28 days. [17][18][19] However, a study addressing the critical issue of the rate of anastomosis using engineered vessels formed by EPCs has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%